Q: 2n plus 3 equals 5n-2

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3 + 3n = 9 + 2n + 4n n = -2

n= -2

Because n = 101.5

5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3

5n2 + 17n + 6 is a quadratic expression. It can be factorised as 5n2 + 17n + 6 = (5n + 2)(n + 3). The expression can be expressed as equal to to a fixed or variable amount when it becomes a function of n. Example : 5n2 + 17n + 6 = 7 or y = 5n2 + 17n + 6

Related questions

3 + 3n = 9 + 2n + 4n n = -2

n= -2

Because n = 101.5

5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3

6n -3=2n+9 6n-2n=9+3 4n=12 n=12/4 n=3

10n + 3 = 7n + 53n = 2n = 2/3

5n2 + 17n + 6 is a quadratic expression. It can be factorised as 5n2 + 17n + 6 = (5n + 2)(n + 3). The expression can be expressed as equal to to a fixed or variable amount when it becomes a function of n. Example : 5n2 + 17n + 6 = 7 or y = 5n2 + 17n + 6

5-2n=3 -2n=3-5 -2n=-2 n=1

3n+3=n+7 3n+3-n=n+7-n (subtract n from both sides) 2n+3=7 2n+3-3=7-3 (subtract 3 from both sides ) 2n=4 2n/2=4/2 (divided by 2 on both the sides) n=2 Answer: n=2

n + 2 = 5, solve for n.n = 5 - 2n = 3

Solve for n. 2n+3=0 2n=-3 n=-3/2

2n + 3 = 352n = 35 -32n = 32n = 32/2n = 16